Development of and mutations for integrase inhibitor resistance in a patient undergoing treatment for pulmonary tuberculosis: A case report - Luís Arthur Brasil Gadelha Farias; Melissa Fiuza Saboya; Natália Ponte Fernandes; Lauro Vieira Perdigão Neto; Erico Antonio Gomes de Arruda (SAGE Open Medical Case Reports, 2023)
Background: Failure of first-line regimens with dolutegravir, a high genetic barrier antiretroviral of the integrase inhibitor class, although uncommon, tends to increase in prevalence due to broader use. Objective: To describe the clinical case of an HIV/Tuberculosis coinfected patient who developed Human Immunodeficieny Virus (HIV) treatment failure during dolutegravir therapy. Case report: Male, 29 years old, presented with a right cervical mass, dry cough, and hyporexia, which lasted 2 weeks. Diagnostic tests were positive for tuberculosis and HIV. The viral load was 437,927 cp/mL (Log = 5.64). Antiretroviral therapy was initiated with Tenofovir/Lamivudine and Dolutegravir (TDF/3TC and DTG), the latter at a dose of 50 mg/day, as was a regimen for tuberculosis. After 8 months, therapeutic failure was verified. Genotyping was requested, with detection of the H51Y and E157Q mutations in the integrase. Conclusion: Attention when determining the antiretroviral therapy treatment regimen of HIV/TB coinfected patients is paramount. Poor adherence to antiretroviral therapy and follow-up may have contributed to treatment failure and resistance.